The strength of a people : the idea of an informed citizenry in America, 1650-1870 - Brown, Richard D. (University of North Carolina Press, 1996)
Thomas Jefferson's conviction that the health of the nation's democracy would depend on the existence of an informed citizenry has been a cornerstone of our political culture since the inception of the American republic. Even today's debates over education reform and the need to be competitive in a technologically advanced, global economy are rooted in the idea that the education of rising generations is crucial to the nation's future. In this book, Richard Brown traces the development of the ideal of an informed citizenry in the seventeenth through nineteenth centuries and assesses its continuing influence and changing meaning.
Keywords: Political science -- United States -- History.; Political socialization -- United States -- History.; Freedom of information -- United States -- History.; Civics -- Study and teaching -- United States -- History.; Socialisation politique -- États-Unis -- Histoire.; Liberté d'information -- États-Unis -- Histoire.; Éducation à la citoyenneté -- États-Unis -- Histoire.; SOCIAL SCIENCE -- Anthropology -- Cultural.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Popular Culture.; Civics -- Study and teaching; Freedom of information; Political science; Political socialization; United States; Burgerschap.; Vorming.; History